Targeted analysis of circRNA expression in patient samples by lexo-circSeq - Naarmann-de Vries, Isabel S.; Eschenbach, Jessica; Schudy, Sarah; Meder, Benjamin; Dieterich, Christoph (Frontiers in molecular biosciences, 2022)
Recently, circular RNAs (circRNAs) have been extensively studied in animals and plants. circRNAs are generated by backsplicing from the same linear transcripts that are canonically spliced to produce, for example, mature mRNAs. circRNAs exhibit tissue-specific expression and are potentially involved in many diseases, among them cardiovascular diseases. The comprehensive analysis of circRNA expression patterns across larger patient cohorts requires a streamlined and cost-effective workflow designed to meet small input requirements. In this article, we present Lexo-circSeq, a targeted RNA sequencing approach that can profile up to 110 circRNAs and their corresponding linear transcripts in one experiment. We established Lexo-circSeq employing total human heart RNA and show that our protocol can detect depletion of a specific circRNA in hiPSC-derived cardiomyocytes. Finally, Lexo-circSeq was applied to biopsies from patients diagnosed with dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM), respectively. Interestingly, our results indicate that circular-to-linear-ratios for circSLC8A1 and circRBM33 are deregulated in cardiomyopathy.
Gesehen am 20.09.2022